2018
DOI: 10.3390/su10082834
|View full text |Cite
|
Sign up to set email alerts
|

More than Yield: Ecosystem Services of Traditional versus Modern Crop Varieties Revisited

Abstract: Agricultural intensification with modern plant breeding focuses on few high-yielding crops and varieties. The loss of traditional crop species and variety diversity contributes to the current decline of provisioning, regulating, and cultural ecosystem services, as reported in the Millennium Ecosystem Assessment. Access to local and adapted varieties is pivotal for resilient agroecosystems, in particular under current global change. We reviewed the scientific literature to understand the role of different crop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 59 publications
0
58
0
1
Order By: Relevance
“…Barthel et al [20] described the development of our agricultural landscapes as an "ongoing and accelerating generational amnesia of traditional practices and experiences", which is detrimental to biodiversity and ecosystem services. The (re-)integration of adapted landraces though was shown to provide numerous cultural and traditional values, along with reinforcing social-ecological resilience [72].…”
Section: Question 3: Improvements Of Agricultural Landscapes For Cesmentioning
confidence: 99%
“…Barthel et al [20] described the development of our agricultural landscapes as an "ongoing and accelerating generational amnesia of traditional practices and experiences", which is detrimental to biodiversity and ecosystem services. The (re-)integration of adapted landraces though was shown to provide numerous cultural and traditional values, along with reinforcing social-ecological resilience [72].…”
Section: Question 3: Improvements Of Agricultural Landscapes For Cesmentioning
confidence: 99%
“…Wheat landraces are among the most suitable germplasm resource where the genetic variation required to that end can be searched [1] and utilized through a pre-breeding process. These locally adapted varieties, traditionally grown with less artificial resource inputs, are genetically diverse repositories of unique traits that have evolved in local environments, which cover a wide range of biotic and abiotic conditions [2,3]. Different studies have shown that Mediterranean wheat landraces represent a particularly important group of genetic resources, where extensive genetic variability as well as tolerance to drought, resistance to diseases and adaptability to low-input farming systems have been documented (see review [3]).…”
Section: Introductionmentioning
confidence: 99%
“…The main cause of genetic erosion, according to the Food and Agriculture Organization of the United Nations [1], is the replacement of local varieties with modern varieties. Modern varieties are preferred over landraces (locally adapted, traditional plant varieties, or farmers' varieties) because they typically provide higher benefits to producers, such as crop yield [2]. Contrary to modern varieties, landraces tend not to be genetically uniform and contain high levels of genetic diversity [1].…”
Section: Introductionmentioning
confidence: 99%